2023
DOI: 10.3390/ma16114037
|View full text |Cite
|
Sign up to set email alerts
|

Protective Performance of Coated Reinforcement in Coral Concrete under Dry/Wet Cycling

Abstract: The actual protective performance of the coated reinforcement in coral concrete was investigated by measuring the chloride ion diffusion coefficient, electrochemical analysis, and numerical simulation. The test results show that the corrosion rate of coated reinforcement in coral concrete under the action of wet and dry cycles is kept at a low level, and the Rp value is always greater than 250 kΩ·cm2 during the test period, which is in the uncorroded state and has good protection performance. Moreover, the chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…Su Chen et al [16] found that the compressive failure mode of coral concrete is not affected by the type of coral aggregate. Cao, H et al [17] found that coral concrete and coral concrete that has been treated with alkali fail in the same way under uniaxial compression and that all coral reefs are completely crushed. Su Weiwei [18] et al found that coral aggregate concrete exhibits higher early strength and better fatigue and impact resistance compared to the same natural concrete strength grade.…”
Section: Introductionmentioning
confidence: 99%
“…Su Chen et al [16] found that the compressive failure mode of coral concrete is not affected by the type of coral aggregate. Cao, H et al [17] found that coral concrete and coral concrete that has been treated with alkali fail in the same way under uniaxial compression and that all coral reefs are completely crushed. Su Weiwei [18] et al found that coral aggregate concrete exhibits higher early strength and better fatigue and impact resistance compared to the same natural concrete strength grade.…”
Section: Introductionmentioning
confidence: 99%
“…The water absorption and corrosion resistance capacity of marble powderenhanced concrete revealed that adding ultra-hydrophobic marble powder decreased the concrete water absorption by 36.42% compared to conventional concrete. Electrochemical experiments revealed that the use of 20% super hydrophobic marble powder increased the polarization resistance of the mortar by 4x10 ⁴ KΩ•cm² more than ordinary mortar, showing that the marble powderbased concrete could be helpful in offshore concrete structures [16,17]. Crumb rubber, a marble powder industry, is also incorporated in concrete as a supplementary cementitious material.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [23] concluded that the diffusion coefficient of chloride ions was highest when using a dry-to-wet ratio of 3:1 by observing the transport characteristics of chloride ions in concrete under four dry-to-wet ratios such as 1:1, 3:1, 5:1, and 7:1. Cao et al [24] investigated the chloride ion transport process in coral concrete under dry and wet cycling and explored the corrosion pattern of steel reinforcement in coral concrete. Meanwhile, the increase in the number of wet and dry cycles will significantly accelerate the diffusion of chloride ions [25].…”
Section: Introductionmentioning
confidence: 99%